EXPLORATORY STUDY ON THE USE OF STORY METHODS IN INCREASING STUDENT INVOLVEMENT IN HISTORY LEARNING AT SMAN 1 MEDAN - Panjaitan, Ruth Novia Hartati; Sumantri, Pulung; Nasution, Imsar Muda (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This research aims to investigate the use of the story method in increasing student involvement in history learning at SMA Negeri 1 Medan. The story method is an approach that utilizes narrative to bring historical content to students in an interesting and engaging way. This research uses a qualitative approach with an exploratory study design. Data was collected through classroom observations, interviews with history teachers, and questionnaires given to students. Data analysis was carried out using content analysis techniques. The research results show that using the story method can increase student involvement in history learning. Students responded positively to the use of narrative in understanding historical content and felt more involved and enthusiastic in the learning process. The implications of this research provide encouragement for history teachers to consider using the story method as an effective learning strategy for increasing student engagement in history lessons. The story method also encourages students to think critically and reflectively. They are invited to see multiple points of view and understand the complexity of historical events, which helps them develop analytical and critical skills. The use of stories creates a more inclusive and enjoyable classroom atmosphere. Students feel more involved and valued, which in turn increases their motivation to study history. However, this research also identified several challenges in implementing the story method, such as the need for additional time to design interesting and relevant story material as well as differences in student learning preferences. However, these challenges can be overcome through collaboration between teachers and support from the school. Overall, this research concludes that the story method is an effective and innovative learning strategy for increasing student involvement in history learning. The recommendation put forward is to continue developing and perfecting this method, as well as providing training and workshops for teachers so that they are more skilled in implementing the story method. In this way, it is hoped that history learning in high schools can become more interesting, interactive and meaningful for students and help them develop a deeper understanding and appreciation of history.